2003
DOI: 10.1152/japplphysiol.00525.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bronchodilator particle size in asthmatic patients using monodisperse aerosols

Abstract: Aerosol particle size influences airway drug deposition. Current inhaler devices are inefficient, delivering a heterodisperse distribution of drug particle sizes where, at best, 20% reaches the lungs. Monodisperse aerosols are the appropriate research tools to investigate basic aerosol science concepts within the human airways. We hypothesized that engineering such aerosols of albuterol would identify the ideal bronchodilator particle size, thereby optimizing inhaled therapeutic drug delivery. Eighteen stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 31 publications
3
41
0
1
Order By: Relevance
“…Drugs that target receptors in the large airways would benefit from larger particles. 15 Laube et al reported a significant increase in intrapulmonary deposition in small and medium size aerosols when a slow inhalation maneuver was used. 11 The limitations of this study are related to its in vitro nature and the methodology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drugs that target receptors in the large airways would benefit from larger particles. 15 Laube et al reported a significant increase in intrapulmonary deposition in small and medium size aerosols when a slow inhalation maneuver was used. 11 The limitations of this study are related to its in vitro nature and the methodology.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the change of aerosol particle size could affect the deposition location and therefore increase systemic absorption and decrease the therapeutic response. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Studies with a similar protocol were undertaken in mild to moderate asthmatics, 82,83 using monodisperse albuterol aerosols of 1.5 μm, 3 μm, and 6 μm. The results of the first of the investigations, by Usmani et al, 83 differed from those of Zanen et al, [79][80][81] because bronchodilator response was found to be higher for 3 μm and 6 μm aerosols than for the 1.5 μm aerosol.…”
Section: Monodisperse Pharmaceutical Aerosol Studiesmentioning
confidence: 99%
“…In particular, it is still unknown what is the optimal particle size able to provide greater improvements in lung function. In this regard, the discrepancy between the study from Zanen et al [13] and that from Usmani et al [14] which specifically addressed the clinical benefit as a function of the particle size of the inhaled bronchodilator, could be only apparent, since the asthmatic volunteers differed in terms of magnitude of airway obstruction. Findings with this methodology generally replicate those obtained with the Andersen impactor device.…”
Section: Comparing Devices For Chronic Obstructive Pulmonary Diseasesmentioning
confidence: 94%